Moroccan Hybotinae (Diptera: Hybotidae): first record of the subfamily and rare genera with an emphasis on their distribution - Zouhair, Laila; Kettani, Kawtar (Zootaxa, 2022)
Entomological surveys in the Moroccan Western Rif have led to record the subfamily Hybotinae for the first time in Morocco, with two species of the genus Hybos Meigen (Hybos culiciformis Fabricius and Hybos striatellus Villeneuve), and one species of Syndyas Loew (Syndyas subsabinios Chvála) recorded for the first time from Africa, and constitutes the first occurrence of the genus Syndyas in North Africa. In addition, Chillcottomyia Saigusa and Lamachella Melander are recorded for the first time from the Mediterranean Region with two undescribed species represented by single females. A key of Moroccan Hybotinae genera is provided.